Risk Factors and Case Management of Acute Diarrhoea in North Gondar Zone, Ethiopia - Mediratta, Rishi P; Feleke, Amsalu; Moulton, Lawrence H; Yifru, Sisay; Sack, R Bradley (Journal of Health, Population and Nutrition, 2010)
In Ethiopia, evidence is lacking about maternal care-taking and environmental risk factors that contribute to acute diarrhoea and the case management of diarrhoea. The aim of this study was to identify the risk factors and to understand the management of acute diarrhoea. A pretested structured questionnaire was used for interviewing mothers of 440 children in a prospective, matched, case-control study at the University of Gondar Referral and Teaching Hospital in Gondar, Ethiopia. Results of multivariate analysis demonstrated that children who were breastfed and not completely weaned and mothers who were farmers were protective factors; risk factors for diarrhoea included sharing drinking-water and introducing supplemental foods. Children presented with acute diarrhoea for 3.9 days with 4.3 stools per day. Mothers usually did not increase breastmilk and other fluids during diarrhoea episodes and generally did not take children with diarrhoea to traditional healers. Incorporating messages about the prevention and treatment of acute diarrhoea into child-health interventions will help reduce morbidity and mortality associated with this disease. Key words: Case-control studies; Case management; Diarrhoea, Acute; Oral rehydration solution; Prospective studies; Risk factors; Ethiopia DOI: 10.3329/jhpn.v28i3.5552 J HEALTH POPUL NUTR 2010 Jun;28(3):253-263